2021
DOI: 10.4315/jfp-20-203
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Virulence and Resistance Genes in Salmonella in Cloacae of Slaughtered Chickens and Ducks at Pluck Shops in Trinidad

Abstract: The study used PCR to determine the molecular basis of the antibiotic resistance and virulence profiles of isolates of Salmonella by targeting genes encoding for carriage and persistence in the poultry.  A total of 1503 cecal samples from poultry were collected, 91 (6.1%) were positive for Salmonella spp. Ten different serotypes were detected from Salmonella isolates.  The study was also conducted to determine the occurrence of 13 virulence and 12 resistance genes in isolates of Salmonella spp. All  46 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
3
8
2
Order By: Relevance
“…Both invA and sopE are encoded by SPI-1, which is involved in host invasion, and the frequency of detection of sopE (79.1%) in the current study is lower than the 99% found in chickens in Brazil (Borges et al, 2013) but higher than the 67.7% detected in Trinidad (Kumar et al, 2021). SopE, an effector for translocation, contributes to the expression of Salmonella invasion by stimulating membrane ruffling (Bakshi et al, 2000).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Both invA and sopE are encoded by SPI-1, which is involved in host invasion, and the frequency of detection of sopE (79.1%) in the current study is lower than the 99% found in chickens in Brazil (Borges et al, 2013) but higher than the 67.7% detected in Trinidad (Kumar et al, 2021). SopE, an effector for translocation, contributes to the expression of Salmonella invasion by stimulating membrane ruffling (Bakshi et al, 2000).…”
Section: Discussioncontrasting
confidence: 66%
“…The mgtB gene, found in 87.3% of our isolates and 90.9% of the patterns, has been reported at higher frequencies by others elsewhere such as 100% in Trinidad and China (Kumar et al, 2021; Zhang et al, 2018). However, lower frequencies of the mgtB gene have been reported by others (Liu et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We could not find a single study on antimicrobial resistance genes in Salmonella from pigs in the Caribbean, and only few on Salmonella as a whole in the Caribbean. In poultry strains in Trinidad, a quite higher prevalence of resistance was found compared to our study, and this included plasmid-mediated colistin resistance [36][37][38].…”
Section: Discussioncontrasting
confidence: 63%